THE REGGIO EMILIA APPROACH IN RESPONDING TO 21ST CENTURY CHALLENGES TO EARLY CHILDHOOD CAPABILITIES - Muslim; Atok Miftachul Hudha (El Midad, 2026)
In the 21st century, everyone faces challenges of globalization, including young children. Based on previous research, abilities can be developed through a child-centered approach. The Reggio Emilia Approach is one of those. Reggio Emilia uses project-based learning and open-ended materials to develop 21st-century skills. However, the Reggio Emilia Approach has another component that may also be developed to strengthen those abilities. This study aims to see whether all the Reggio Emilia components can address the challenges and to assess the feasibility of applying this approach in the Indonesian context. This study uses a literature review method, analyzing 2 primary sources on the Reggio Emilia Approach, 1 primary source on Education according to Ki Hajar Dewantara, and 62 articles, including primary and secondary sources, on the Reggio Emilia Approach and 21st-century skills.